2022
DOI: 10.1108/oth-10-2021-0117
|View full text |Cite
|
Sign up to set email alerts
|

Integrating crisis learning into futures literacy – exploring the “new normal” and imagining post-pandemic futures

Abstract: Purpose Crises are major events or periods faced by individuals, groups and society. This paper aims to explore the value of facilitating (un)learning in and from crises. Educators have a key role in building futures literacy (FL) for dealing with uncertainties, understanding emergence and responding to rapid, complex change. Integrating crisis learning as part of FL is important for enhanced anticipatory and crisis responses. Design/methodology/approach Adapting from causal layered analysis (CLA) methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
(27 reference statements)
1
9
0
1
Order By: Relevance
“…During crisis requiring improvisational handling in an organisation, there is a high potential for individual learning and increased discretion performing tasks. The opportunities for learning and transformation during dramatic changes are also found in other research as reported by Karjalainen et al (2022). Another reflection from our findings is the means of involvement, trustful relations, information and communication that influence the expected results and desired outcomes.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…During crisis requiring improvisational handling in an organisation, there is a high potential for individual learning and increased discretion performing tasks. The opportunities for learning and transformation during dramatic changes are also found in other research as reported by Karjalainen et al (2022). Another reflection from our findings is the means of involvement, trustful relations, information and communication that influence the expected results and desired outcomes.…”
Section: Discussionsupporting
confidence: 86%
“…In the wake of the COVID-19 pandemic, the capacity for learning and innovation has been identified as a crucial component in strategies for organisational change and human resource development ( Dirani et al, 2020 ; Karjalainen et al, 2022 ; Laitinen and Ihalainen, 2022 ; McLean and Jiantreerangkoo, 2020 ; Yawson, 2020 ). Because of the rapid progress of the pandemic, many organisations have been forced to respond swiftly to the changing circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…The transformative role of education is increasingly recognized, prompting inquiries into the framework for these new models. One study sought to identify how teachers perceive the future and how they can respond to uncertainty and complex changes (Karjalainen et al, 2022). Educational systems and policymakers are exploring ways to create a more inclusive, relevant and effective approach to education in the 21st century (Foster and Piacentini, 2023).…”
Section: External and Internal Validation In Educational Modelsmentioning
confidence: 99%
“…Recent rapid changes and a number of events coined as crises, lacking adequate governance measures, have raised suggestions to integrate crisis awareness as part of futures literacy [ 30 ]. We suggest that crises reflect a VUCA world, as they have become more rapid and combined.…”
Section: Hybridisation and Anticipatory Governancementioning
confidence: 99%